Power lines and the public perception - Wall, Carlos Alberto (2011)
The interconnections between electrical systems are a “technical and economic need” in order to facilitate the use and optimization of the energy sources and to improve the supply guarantee. At the same time, transmission lines are the most extended works of the electrical networks, having to carefully analyze their design and line routes since some serious impacts and/or conflicts can be caused or increased due to their location. The space occupancy and the visual perturbation are primary factors of overhead line impact in the environment. On the other hand, the electric (E) and magnetic (B) fields produced by electrical installations have become of great concern to the population, provided their possible link with health aspects. From the environmental point of view, the implantation of a new electrical infrastructure constitutes an intrusion in the landscape that may give rise to a decrease in the quality of the landscape of the location where it is inserted. Such visual impact is directly related with visibility level of the new shape introduced in the land and with the contrast between this and the original landscape. It is possible to assess the capacity of a landscape to absorb certain modifications, minimizing the alterations in the visual qualities that the viewer perceives. This paper shows the procedures followed in local cases where analysis of levels of electrical and magnetic fields and of visual landscapes has been incorporated to electrical project planning and works of electrical projects of 500 kV in AC and ±600 kV in DC.